Voting on meritocracy. - Gradstein, Mark (European Economic Review, 2004)
This paper considers a setting where a resource such as education budget is to be distributed among agents. The latter differ in their ability to make use of the resource, and the issue is that of determining the allocation rule whereby the individual shares of the resource (may) depend on their relative efforts of obtaining it. The paper's focus is on endogenous determination, through voting, of the degree of meritocracy in the resource allocation system, which determines the marginal productivity of one's effort. It is found that a meritocratic system is expected to be supported by highly productive individuals and opposed by those with low productivity. When the decision making becomes less elitist and involves broader participation of population groups the support for meritocracy decreases. Copyright (c) 2003 Elsevier B.V.